Implementing the Jigsaw Cooperative Learning Model to Suport Mathematics Learning Outcomes: A Qualitative Study at Eighth-Grade Student SMP Muhammadiyah Lumajang - Anisa Desti Ramadhani; Fahmi Abdul Halim; Devi Rahayu Agustin; Fatqurhohman; Zaenal Arifin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Mathematics learning in secondary schools is often characterized by teacher-centered instruction, resulting in limited student participation and suboptimal learning outcomes. This study aims to investigate the implementation of the Jigsaw Cooperative Learning Model in mathematics learning at SMP Muhammadiyah Lumajang. A qualitative descriptive approach was employed involving an eighth-grade mathematics teacher and students as research participants. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the Jigsaw Cooperative Learning Model was implemented systematically through lesson planning, expert-group discussions, peer teaching, and classroom evaluation. The implementation promoted active student participation, collaborative learning, and improved conceptual understanding of mathematics. Teacher competence, students' learning motivation, collaborative classroom interactions, and adequate learning facilities supported the implementation, while limited instructional time, differences in students' academic abilities, and varying levels of self-confidence were identified as the main challenges. The study concludes that the Jigsaw Cooperative Learning Model provides an effective student-centered learning environment that supports active engagement and contributes positively to mathematics learning in junior secondary education.